The impact of emotional intelligence and cultural intelligence on job performance in Russia - Engle, Robert; Dimitriadi, Nikolay; Toskin, Katarzyna (Journal of Management Policy and Practice, 2026)
A great deal of work has been done in recent decades examining the impact of emotional intelligence (EQ) and cultural intelligence (CQ) on extra-role job performance. However, little of this research has used both EQ and CQ constructs together in the same analytical model. In addition, the available literature in is virtually silent with regards to the relationships of these constructs in Russia, a country with a significant multicultural environment. This study examines these relationships, using a sample of 189 supervisory and non-supervisory subjects in Russia. The results suggest that motivational CQ may be seen as an antecedent of CQ and EQ, both of which significantly impact extra-role job performance. EQ and CQ factors were also found to mediate the relationship between motivational CQ and extra-role job performance. In addition, necessary condition analysis was completed adding to model insights. These results extend our knowledge to a Russian sample, and not only support the Thomas et al. (2015) approach to CQ, but also suggest significant implications for current EQ-CQ model theories.
Keywords: Antecedent (behavioral psychology); Cultural intelligence; Emotional intelligence; Job performance; Multiculturalism; Sample (material); dept.bis

An exploratory analysis of equally male/female-owned firm performance in the United States - Toskin, Katarzyna; Jocic, Marko (International Journal of Entrepreneurial Behaviour & Research, 2025)
Keywords: Business performance; Census; Entrepreneurship; Equally male/Female-owned firms; Exploratory analysis; Exploratory research; Family businesses; Firm ownership; Gender; Outcome (game theory); Sample (material); Test (biology); Variance (accounting); dept.bis

Undergraduate Business Analytics and the Overlap with Information Systems Programs - Ceccucci, Wendy; Jones, Kiku; Toskin, Katarzyna; Leonard, Lori (Information Systems Education Journal, 2020)
As companies continue to put data and business analytics as their top priority, universities will need to supply students with the appropriate skill sets that meet this demand and offer future opportunities to their graduates. Although business analytics is a new field, many of the required competencies stem from already established areas such as Information/Computer Technology or Information Systems. Using a sample of 225 randomly selected AACSB accredited business schools this study examined the new developments in Business Analytics undergraduate academic programs, and determined the amount of overlap between the Business Analytics and the Information/Computer Technology degree programs. Our findings reveal that approximately 36 percent of the Business Analytics programs overlap with the Information/Computer Technology programs. In addition, the top three required courses in most Business Analytics programs include a Database course, predictive analytics course, and Introduction to Business Analytics. This research provides valuable insight for schools that haven't adopted a Business Analytics degree yet or are looking to improve their existing curriculum. In addition, colleges and universities can now utilize the appropriate Information Systems courses and include them as important foundation and part of their Business Analytics programs.
ERIC Number: EJ1258206
Keywords: Business Administration Education; Business Schools; College Curriculum; Computer Science Education; Elective Courses; Information Technology; Required Courses; Undergraduate Study; dept.bis; peer-reviewed; ⛔ No DOI found

Information Technology Work Value Differences - Toskin, Katarzyna; McCarthy, Richard V. (Journal of Computer Information Systems, 2021)
This study investigates reasons behind high employee turnover of IT professionals through the value placed on intrinsic, extrinsic, leisure, and social rewards. It addresses two questions; what are the most preferred work values by IT professionals, and how do they differ from other professions. Data was collected via a survey using subjects from Amazon Mechanical Turk. A sample of 380 respondents was used. Key findings reveal that intrinsic rewards were the most important work values for IT professionals followed by leisure, extrinsic, and social rewards. Furthermore, when compared to the preferences of non-IT professionals, the levels of preferences for intrinsic rewards were statistically significantly higher for IT professionals than all other professions. This study provides valuable insight regarding key motivating factors of IT professionals and offers practical implications for practitioners relating to job characteristics that are most likely to reduce IT turnover and rethink their rewards systems.
_eprint: https://doi.org/10.1080/08874417.2019.1639567
Keywords: IT employee motivation; Information technology; dept.bis; peer-reviewed; turnover; work values

Flow through Regression: A Guide to Interpreting and Communicating Regression Models for Data Analytics Students - Toskin, Katarzyna; Kunene, Niki (Information Systems Education Journal, 2021)
Faculty teaching data analytics at undergraduate level are often faced with the tension created by student under-preparedness, the demands of the course, and time constraints. How do faculty close this gap? In this paper, we propose the use of flow diagramming as an accessible method for interpreting regression analyses, in ways that are time efficient and not alienating to the student. Our study shows that the use of such flow diagrams has a positive effect on student understanding without additional remedial instruction. Time saved can be directed at core learning objectives of the analytics.
ERIC Number: EJ1319909
Keywords: Business Administration Education; College Faculty; College Preparation; Data Analysis; Pretests Posttests; Remedial Instruction; Statistics Education; Teaching Methods; Time Management; Undergraduate Students; Visual Aids; dept.bis; peer-reviewed; ⛔ No DOI found

Emotional and Cultural Intelligences' Impact on Extra-Role Job Performance in Russia - Engle, R. L; Dimitriadi, N.; Toskin, K (International Business: Research, Teaching, and Practice, 2021)
Keywords: dept.bis; ⛔ No DOI found

An Approach for Ushering Logistic Regression Early in Introductory Analytics Courses - Kunene, Niki; Toskin, Katarzyna (Information Systems Education Journal, 2022)
Logistic regression (LoR) is a foundational supervised machine learning algorithm and yet, unlike linear regression, appears rarely taught early on, where analogy and proximity to linear regression would be an advantage. A random sample of 50 syllabi from undergraduate business statistics courses shows only two percent of the courses included LoR. Conceivable reasons for this dearth of LoR content is likely related to topic complexity, time constraints, and varying degrees of tool ease of use and support. We propose that these constraints can be countered by: [1] introducing logistic regression early, [2] informed tool selection prioritizing ease of use with comprehensive output, and [3] using/developing innovative, accessible, and easy to understand concept learning aids. This approach would leverage the proximity to linear regression and probability readily embed distributed practice for student understanding of a foundational technique.
ERIC Number: EJ1363423
Keywords: Business Administration Education; Comparative Analysis; Concept Formation; Course Content; Course Descriptions; Goodness of Fit; Institutional Characteristics; Introductory Courses; Private Colleges; Probability; Regression (Statistics); State Universities; Statistics Education; Teaching Methods; Two Year Colleges; Undergraduate Students; Universities; Usability; dept.bis; peer-reviewed; ⛔ No DOI found

Impact of emergent technologies on US workforce: exploratory analysis. - Toskin, Katarzyna (Journal of Information Systems Applied Research, 2023)
Keywords: dept.bis; peer-reviewed; ⛔ No DOI found

The Evolving Landscape of International Consumer Data Privacy Compliance. - Pisano, Mark; Smith, Robert A.; Badr, Kauther S. (ACET Journal of Computer Education & Research, 2022)
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

Using a Multilingual Chatbot for Foreign Language Practice. - Vanjani, Mahesh; Aiken, Milam; Park, Mina (Issues in Information Systems, 2020)
Keywords: dept.bis; peer-reviewed; ⛔ No DOI found

The Unintentional Risk or Liability of Implementing Deploying, or Adopting a Private Blockchain Network - Pisano, Mark; Bassett, Richard (ACET Journal of Computer Education and Research, 2021)
Keywords: dept.bis; peer-reviewed; ⛔ No DOI found

Organizational Cost and Complexity Saving Opportunities via the Development, Deployment, and Implementation of Blockchain Networks - Pisano, Mark; Bassett, Richard (Information Technology and Management Science, 2021)
Blockchain is being promoted as the platform to disrupt business as usual in many transaction-heavy sectors. Questions remain about the future standards of blockchain, their feature set, functionality, and the willingness of organisations to disrupt their existing revenue streams via blockchain. The most significant near-term promise that affords industry is the cost and complexity savings via the standardization of their technology infrastructure stacks. This paper explores the benefits available of reduced costs and complexity via the adoption of blockchain.
Number: 1
Keywords: Blockchain; banking; deployment; dept.bis; human capital; industries; peer-reviewed

Property Management – An Industry of Fragmented Technology Solutions - Bassett, Richard; Pisano, Mark (Information Technology and Management Science, 2022)
Successful property management, which can be done by individual owners or by professional property managers, has numerous interrelated complex business processes: tenant attraction, screening, leasing, tenant move-in, property maintenance, retention/lease renewals, tenant move-out, and reputation management. Property managers must be highly skilled communicators and thoroughly understand the legal implications of housing and contract law in their operating environments. The lack of affordable solutions available to small and mid-sized property managers drives their use of fragmented technology solutions provided by numerous technology vendors that employ redundant data-gathering methods, putting them at a competitive disadvantage. This research paper explores the information systems needs of property managers in contrast to the solutions available to them in the marketplace.
Number: 1
Keywords: Automated business process; dept.bis; fragmented technology solutions; peer-reviewed; property leasing; property management; property marketing

Teaching tip GetVirtual: A universal service-based learning framework - Toskin, K.; Pisano, M.A.; Corey, T. (Journal of Information Systems Education, 2023)
This paper introduces a universal framework for service-based learning which provides information systems students with opportunities to gain invaluable hands-on experience. More specifically, through this framework, students can develop hard, soft, and interdisciplinary skills in preparation for their first professional careers upon graduation. In addition to introducing the framework, we provide student testimonials and feedback as well as lessons learned from our experience in efforts to prepare and help other schools interested in offering similar growth opportunities to their students to have a smooth and successful implementation. © 2023, Journal of Information Systems Education. All Rights Reserved.
Keywords: Experiential learning & education; Framework; GetVirtual; Service-learning; Teaching tip; dept.bis; peer-reviewed; ⛔ No DOI found

An economic model of machine translation - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2021)
1 citations (Crossref) [2023-10-31]
Keywords: dept.bis; peer-reviewed

A comparison of two multilingual meeting systems - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: Google Translate; dept.bis; dept.mgt; peer-reviewed